Reference Agent : Mengoptimalkan Pustakawan Dalam Menghidupkan Kembali Layanan Referensi - Kristyanto, Dian (STAIN Ponorogo, 2015)
One of the services developed in library is reference service. This service is a featured product that can give information solution for users. For the vital service, reference librarian is demanded to have an innovation, creation and communication skill, so he can serve to user needs for information. This article dealts with the concept of reference librarian to the development of ICT in order to be agent of reference service being a featured service of library.